2000
DOI: 10.1063/1.1287056
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear shielding constants by density functional theory with gauge including atomic orbitals

Abstract: Recently, we introduced a new density-functional theory ͑DFT͒ approach for the calculation of NMR shielding constants. First, a hybrid DFT calculation ͑using 5% exact exchange͒ is performed on the molecule to determine Kohn-Sham orbitals and their energies; second, the constants are determined as in nonhybrid DFT theory, that is, the paramagnetic contribution to the constants is calculated from a noniterative, uncoupled sum-overstates expression. The initial results suggested that this semiempirical DFT approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
117
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(117 citation statements)
references
References 29 publications
0
117
0
Order By: Relevance
“…Other investigations on molecular systems have shown that calculated shielding parameters are highly dependant on the type of XC functionals. [106][107][108][109][110] Linear response of crystalline or molecular orbitals to the magnetic field perturbation are strongly dependant on the occupied-virtual energy gap (E gap ) and the shape of the virtual orbitals, through the first-order corrected wave function (Eq. 14).…”
Section: B Improvement Of Dft Calculationsmentioning
confidence: 99%
“…Other investigations on molecular systems have shown that calculated shielding parameters are highly dependant on the type of XC functionals. [106][107][108][109][110] Linear response of crystalline or molecular orbitals to the magnetic field perturbation are strongly dependant on the occupied-virtual energy gap (E gap ) and the shape of the virtual orbitals, through the first-order corrected wave function (Eq. 14).…”
Section: B Improvement Of Dft Calculationsmentioning
confidence: 99%
“…For the DFT calculations we employed the BP86(VWN) functional [16][17][18] with the SG-1 grid [19] for the numerical integrations [20]. NMR calculations were performed using the 6-31G * * [21,22] basis with our linear-scaling method [7,8] at the GIAO-HF [23][24][25][26][27] and GIAO-DFT [28][29][30][31][32][33][34] levels, respectively. Relative NMR shifts are given, unless noted otherwise, with respect to those of a TMS molecule calculated at the same level of theory.…”
Section: Computational Detailsmentioning
confidence: 99%
“…The assignment is supported further by DFTbased ab initio chemical shift calculations using a cluster-model approach, which gives good agreement between experimental and calculated chemical shift values. The 31 P chemical shifts appear to be strongly correlated with the average PÀP bond lengths within the PA C H T U N G T R E N N U N G (P 1/3 ) 3 coordination environments, whereas no clear dependence on average P-P-P bond angles can be detected.…”
Section: Introductionmentioning
confidence: 79%
“…[6,10] High-resolution magic-angle-spinning (MAS) NMR spectroscopy offers a sensitive differentiation between distinct phosphorus environments based on the extremely wide 31 P chemical shift range (d = 300 to À550 ppm in the case of crystalline phosphides). [6, 10d, 11] Despite this sensitivity, to date only a few promising correlations of 31 P chemical shifts with structural characteristics have been shown.…”
Section: Introductionmentioning
confidence: 99%